Magnetic Resonance Imaging Assessment of Gluteal Fat Grafts (2006)
ABSTRACT: Backgrounds: One goal of lipoplasty is to create a round and projected buttock contour. Despite multiple papers evaluating lipoinjection, controversies still remain. Methods: This report describes a series of patients who underwent liposuction, gluteal lipoinjection, and evaluation with magnetic resonance imaging (MRI). From January 2003 to January 2004, the patients scheduled for contour surgery by the investigators were evaluated using MRI, photographic records, and gluteal circumference measurement 1 week before surgery, then 2 weeks and 3 months after the procedure. A statistical analysis was performed for 10 patients who received, on the average, a 350-ml injection of fat obtained during liposuction. Results: Gluteus muscle volume increased, reaching a higher level 2 weeks after the injection than the level 3 months afterward (p < 0.001). The gluteal circumference, modified 2 weeks after surgery by about 1 to 3 cm, came back to previous values 3 months after the procedure (p < 0.05), a phenomena interpreted as reabsorption and resolution of the postoperative edema. There is no correlation between the gluteus muscle volume obtained by MRI and the gluteal circumference (p > 0.05). Conclusions: The findings led to the conclusion that enhancement of the gluteal contour after fat injection results from survival of the injected tissue 3 months after the surgery, which was objectively evaluated by MRI as having a calculated reabsorption rate of 24% to 36%.